تأثير منهج تعليمي وفق التمرينات التوافقية والتغذية الراجعة الخارجية والداخلية في مستوى أداء بعض مهارات الحركات الأرضية في الجمناستك الفني للطالبات - صالح, أ.م.د زانا محمد محمد; الحسين, م. أفاقت خيون عبد (Sulaimani Journal for Humanities, 2023)
The current research aims to: 1 - Recognizing the effect of the educational curriculum according to coordination exercises and external - internal feedback on the level of performance of some floor movement skills of the experimental group. 2- Recognizing the effect of the educational curriculum on the performance level of some floor movement skills of the control group. 3- Identifying the differences between the experimental and control groups in the post tests of the variables investigated. The researchers used the experimental method by designing the two equal experimental and control groups with the pre- and post-test, and the research sample was identified with the third-year students in the Faculty of Physical Education - Koya University for the academic year (2021-2022), and used a set of devices, tools and means of collecting information, which includes (questionnaire, tests and standards) to reach the objectives of the research, then they prepared an educational curriculum according to coordination exercises and external and internal feedback, Statistical means were used to obtain the results (arithmetic mean, standard deviation, t-test for correlated samples, t-test for two independent samples, Cohen's equation to measure the effect size of a correlated sample, the Eta square equation to measure the effect size of two independent samples), The researchers reached the following most important conclusions: 1 - The researched educational curriculum that was applied to the students of the experimental group had a positive effect on the level of technical performance of the skills of standing on hands, the human wheel and the Arab jump. 2- The applied educational method applied to the students of the control group had a positive effect on the level of performance of the skills of the human wheel and the Arab jump. 3 - The superiority of the researched educational curriculum of the experimental group over the educational approach of the control group in the performance level of the handstand skill.